Effects of forest type and stream size on volume and distribution of stream wood: legacies of wildfire in Euro-Mediterranean context - Vaz, Pedro (2014)
Downed wood pieces are key links between terrestrial and aquatic ecosystems. They promote organic matter retention, create habitat, and potentially increase stream productivity. The stock of downed wood in a river system is a product of the interaction between wood supply, transport, in situ losses, and retention characteristics of the system. Fire and forest management are important disturbances that influence the amount and organization of stream wood with boom-and-bust periods of recruitment and fluvial transport processes. We examined 1st- through 3rd-order Portuguese streams flowing through 3 common silvicultural systems in southern Europe: forests of cork oak, eucalyptus, and maritime pine. Our data set included 1483 pieces of wood in 27 streams, all of which had experienced extensive wildfires within the previous 6 y. We used binned neighbor-k analysis to assess wood organization (segregated, random, or aggregated). We then used linear mixed-effects modeling to evaluate the effects of stream order, forest type, and their interaction on wood volume and organization. The best predictor of wood volume and organization was the interaction between forest type and stream order. Most wood pieces were burned and organization was low, suggesting that arrangement of wood was largely a product of input dynamics rather than transport processes at this time. Potential drivers of across-system variability included vegetation obstructions, wood length:channel width ratios, management actions, and effects of fire. Climate models predict more droughts in the Euro-Mediterranean region in the future, with implications for wood volume, transport, and function as terrestrial vegetation invades intermittent stream channels and plant communities shift from managed forests to shrublands with few trees.